Fundamentals of Entrepreneurship (ENT 300) : Everyday printing / Linda Jimek … [et al.] - Jimek, Linda; Paul, Ivy; Samsuddin, Farah Dania; Aban, Noraliza (2011)
There are criteria and conditions that have to be fulfilled which require the involvement of effort and precision of producing our goods. Without such conditions, the business cannot run properly and organizational goals will not be achieved. These conditions must be achieved in order for business to take position in the first place. Firstly, the organization has to attain a business or trade license from related authorities due the organization's location. The organizaHon must be registered and recognized by the particular departments in servicing.